1994
DOI: 10.1037/0021-843x.103.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Personality variables and disorders in anorexia nervosa and bulimia nervosa.

Abstract: All dominant models of the eating disorders implicate personality variables in the emergence of weight concerns and the development of specific symptoms such as bingeing and purging. Standardized measures of personality traits and disorders generally confirm clinical descriptions of restricting anorexics as constricted, conforming, and obsessional individuals. A less consistent picture suggesting affective instability and impulsivity has emerged from the assessment of subjects with bulimia nervosa. Considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
271
2
14

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(315 citation statements)
references
References 95 publications
(126 reference statements)
28
271
2
14
Order By: Relevance
“…In addition, these alterations in postmeal amino acid metabolism are only partly reversed by nutritional rehabilitation (80). It has been speculated (1,12) that there is an anxiety-reducing character to dietary restraint in people with AN. In fact, we have found that the anxiolytic effects of dieting in AN were related to a reduction in 5-HT neurotransmission.…”
Section: Diet and Brain 5-ht Neurotransmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these alterations in postmeal amino acid metabolism are only partly reversed by nutritional rehabilitation (80). It has been speculated (1,12) that there is an anxiety-reducing character to dietary restraint in people with AN. In fact, we have found that the anxiolytic effects of dieting in AN were related to a reduction in 5-HT neurotransmission.…”
Section: Diet and Brain 5-ht Neurotransmissionmentioning
confidence: 99%
“…There is evidence that there is a dysphoria reducing character to dietary restraint (1,12,66) and binge-purge behaviors (119)(120)(121). This would suggest some interaction between pathways regulating appetitive behaviors and emotions.…”
Section: Appetitive Regulationmentioning
confidence: 99%
“…[3][4][5][6] Perfectionism represents a precursor to, and a characteristic of, the acute phases of certain eating disorders. [7][8][9][10] Previous investigations have demonstrated that perfectionism persists after long-term weight recovery from anorexia nervosa (AN), and is present in relatives of women with eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Stice and colleagues (Stice, Akutagawa, Gaggar, & Agras, 2000;Stice, Ziemba, Margolis, & Flick, 1996) emphasized that negative affect and dietary restraint are important triggers for the development of bulimic pathology. Studies have suggested bulimics report more depression, increased anxiety, and lower self-esteem when compared to non-bulimics (Mintz & Betz, 1988;Vitousek & Manke, 1994). Many bulimic women report periods of increased depression, anxiety, and feelings of inadequacy prior to engaging in binge-eating behaviors (Steinberg, Tobin, & Johnson, 1990).…”
Section: Risk Factorsmentioning
confidence: 99%